Black, asian and minority ethnic female business owners: discrimination and social support - Davidson, M.J; Fielden, S. L.; Omar, Azura (Emerald Group Publishing Limited, 2010)
Purpose – The purpose of this paper is to focus on the positive and negative effects of gender and ethnicity in relation to discrimination and the problems encountered in accessing social support (including emotional and instrumental support).